Wives,Widows & Concubines: The Conjugal Family Ideal in Colonial India - Sreenivas,Mytheli (Orient Black Swan, 2009)
The book examines how the family became the centre of intense debates about identity, community, and nation in colonial Tamil Nadu. Developing ideas about love, marriage and desire were inextricably linked to caste politics, the colonial economy, and nationalist agitation. The book argues that notions of community centred around the changing family were fundamental to shaping national identity in the early twentieth century. Emerging earliest among professional and mercantile elites seeking to reform colonial property relations, and fueled by the feminist and anti-caste politics of nationalist movements, this emphasis on conjugality took numerous, sometimes contradictory, forms. On the one hand, conjugality provided a language with which women laid claim to a host of rights, from the right to inherit a deceased husband’s property to the right to seek emotional and sexual fulfillment in marriage. On the other hand, appeals to conjugality also served to reinscribe women’s oppression both inside and outside marriage. Mapping this complex history in relation to the culture, politics, and economy of the Tamil region, the bookopens new arenas of inquiry about the family and colonial modernity in South Asia. Recipient of the Joseph W. Elder Prize in the Indian Social Sciences from the American Institute of Indian studies this book would be of special interest to historians of modern South Asia, as well as anthropologists, sociologists with an interest in women and gender.